Sistematización de un diseño de plan de prevención para los factores de riesgos psicosocial identificados en el Proyecto Nacional de Innovación Tecnológica Participativa y Productividad Agrícola del Ministerio de Agricultura, Ganadería, Acuacultura y Pesca planta central en la ciudad de Quito - Paucar Guerrero, Víctor Paúl (2017)
This systematization of the experience is carried out by developing the format established by the Polytechnic Salesian University, this integrative document gathers the experience of project intervention from the stage of diagnosis, design and execution. In its first partitrefers to its structure, which forms the so-called plan of systematization and a second part is integrated by the experience of systematization, that is to say a reconstruction, it sactors and the actions that were developed for the fulfillment of thesame. The objective of this intervention work was to identify and evaluate psychosocial risk factors and to establish a prevention plan design forth epsychosocial risk factor identified in the Proyecto Nacional de Innovación Tecnológica Participativa y Productividad Agrícola del Ministerio de Agricultura, Ganadería, Acuacultura y Pesca planta central en la ciudad de Quito (Tenorio, 2016). This intervention project was of type and descriptive level of field, it was possible to identify the psychosocial risk factors in the collaborators, using as instrument the ISTAS 21 test, that measured six psychosocial dimensions according to the levels of exposure thatwere most affecting the health of the Employees. Base don’t he identification and evaluation of the psychosocial risks assessed by the ISTAS 21 Test, a preventive plan was designed through preventive workshops for reach psychosocial dimension that was most affecting employees in their working environment.